Cinema, arquitetura e patrimônio: Aquarius e a memória como resistência - Costa, Pedro de Barros Nunes (2023)
The intersection of cinema and architecture offers a unique lens to comprehend the contemporary urban challenges, especially relating to heritage preservation. The urban landscape faces a growing loss of architectural and cultural elements over time. When introduced to the sphere of social memory and places of memory, supported with arguments by authors such as Maurice Halbwachs e Pierre Nora, we come across a central element for the rationalisation of the heritage as an element of place of memory and thus necessary preservation. An analysis of the film Aquarius (2016), directed by Kleber Mendonça Filho, was presented. The film became a primary case study, investigating the relationship between heritage and affective memory through the experience of the character Clara and her emotional bond with the Aquarius building. Through this analysis, it was sought to discern whether the film addresses heritage preservation issues and how it influences the construction of an affective and social memory marked by resistance. The adopted methodology comprehends an analytical and interpretative approach, which manifests itself through a poetic analysis of the film, focusing on scenes which explicitly or implicitly reflect the complexions related to heritage preservation and contemporary urban challenges. These scenes are analysed in the light of concepts such as globalisation, real estate speculation and the architecture of fear, highlighting their impact on the city’s structure and the preservation of memory and heritage. By adopting a poetic approach to the film, this work reveals how cinematographic representations can influence the public understanding about the mentioned issues. The analysis of the film demonstrates the importance of valuing socially relevant places of memory and the need to resist the degradation of cultural heritage. At the end of this work, the results point Aquarius plays a significant role in promoting awareness about heritage preservation, especially when connecting architectural elements with personal and collective memories. Therefore, this study aligns with its general objective of exploring how Aquarius contributes to the construction of an affective and social memory related to resistance and heritage preservation.